Art and book : a commentary on artists' books - Emslie, Anne (Stellenbosch : Stellenbosch University, 2012)
The thesis spans two volumes ... Volume two is an artist's book and although it is part of the project I have set myself, it is not being submitted with the theoretical component of the MA dissertation, but as part of the practical component.' -- Abstract.